Células eletroquímicas: um breve histórico e perspectivas sobre o atual mercado de veículos híbridos e elétricos - Costa, Pedro Vaz Marins [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
With considerable research advances in different technologies aimed at the development/improvement of sustainable means of transport, electrochemical cells (popularly called “batteries”) have been gaining prominence due to their relevance in the industry. In the academic environment, new academic works are performed with the final intention of feeding the heated market, helping the urban mobility sector – from small startups to giants in the automobile industry. In this work, a brief history of electrochemical cells is presented, permeating the different types of batteries, as well as their evolution through the ages. In parallel, it adresses the final destination to which the batteries will be applied, the hybrid and electric vehicles. Thus, a return to past is done, from the appearance of the first electric cars, to the presente, to which this work is presented, revealing the new trends in the sustainable vehicle market and the main technologies currently used.

Com consideráveis avanços de pesquisas em diferentes tecnologias voltadas para o desenvolvimento/aperfeiçoamento de meios de transporte sustentáveis, células eletroquímicas (popularmente denominadas “baterias”) vêm ganhando destaque devido sua relevância na indústria. No meio acadêmico, novos trabalhos são executados com o intuito final de alimentar o mercado aquecido, auxiliando o setor de mobilidade urbana – desde pequenos startups até gigantes no ramo automobilístico. Neste trabalho, apresenta-se um breve histórico das células eletroquímicas, permeando os diferentes tipos de baterias, bem como a evolução das mesmas através das eras. Em paralelo, aborda-se o destino final ao qual as baterias serão aplicadas, os veículos híbridos e elétricos. Assim, faz-se um retorno ao passado, desde o surgimento dos primeiros carros elétricos, até o presente, no qual este trabalho é apresentado, revelando assim as novas tendências do mercado de veículos sustentáveis e as principais tecnologias atualmente utilizadas.
Electrochemical cells: a brief history and perspectives on the current market for hybrid and electric vehicles
Keywords: Electrochemical cells; Batteries; Hybrid vehicles; Electric vehicles; Células eletroquímicas; Baterias; Veículos híbridos; Veículos elétricos; Industria automobilística